Ensuring full participation of people with disabilities in an era of telehealth - Valdez, Rupa S; Rogers, Courtney C; Claypool, Henry; Trieshmann, Lucy; Frye, Olivia; Wellbeloved-Stone, Claire; Kushalnagar, Poorna (Journal of the American Medical Informatics Association : JAMIA, 2021)
The widespread use of telehealth resulting from the COVID-19 pandemic has the potential to further exacerbate inequities faced by people with disabilities. Although, for some members of the disability community, the option to engage with telehealth may result in reduced barriers to care, for others, inadequate attention to the design, implementation, and policy dimensions may be detrimental. Addressing such considerations is imperative to mitigate health inequities faced by the disability community.